A New Risk Factor Profile for Contrast-Induced Acute Kidney Injury in Patients Who Underwent an Emergency Percutaneous Coronary Intervention. (July 2018) - Yuan, Ying; Qiu, Hong; Song, Lei; Hu, Xiaoying; Luo, Tong; Zhao, Xueyan; Zhang, Jun; Wu, Yuan; Qiao, Shubin; Yang, Yuejin; Gao, Runlin
We developed a new risk factor profile for contrast-induced acute kidney injury (CI-AKI) under a new definition in patients who underwent an emergency percutaneous coronary intervention (PCI). Consecutive patients (n = 1061) who underwent an emergency PCI were divided into a derivation group (n = 761) and a validation group (n = 300). The rates of CI-AKI were 23.5% (definition 1: serum creatinine [SCr] increase ≥25% in 72 hours), 4.3% (definition 2: SCr increase ≥44.2 μmol/L in 72 hours), and 7.0% (definition 3: SCr increase ≥44.2 μmol/L in 7 days). Due to the high sensitivity of definition 1 and the high rate of missed cases for late diagnosis of CI-AKI under definition 2, definition 3 was used in the study. The risk factor profile included body surface area <1.6 m 2 ( P = .030), transient ischemic attack/stroke history ( P = .001), white blood cell count >15.00 × 10 9 /L ( P = .047), estimated glomerular filtration rate <60 mL/min/1.73 m 2 ( P = .002) or baseline SCr >133 μmol/L ( P = .007), intra-aortic balloon pump application ( P = .006), and diuretics administration ( P < .001), showing a significant predictive power in the derivation group and validation group. The new risk factor profile of CI-AKI under a new CI-AKI definition in emergency PCI patients is easily applicable with a useful predictive value.